2018
DOI: 10.1097/nan.0000000000000279
|View full text |Cite
|
Sign up to set email alerts
|

A Standard Push-Pull Protocol for Waste-Free Sampling in the Pediatric Intensive Care Unit

Abstract: Blood sampling is a major source of blood loss in the pediatric intensive care unit (PICU). Blood-sparing sampling techniques such as the push-pull method can significantly reduce sampling-related blood loss and protect patients from anemia and blood transfusions. The push-pull method is supported by research evidence for central venous catheter (CVC) sampling, but research protocols differ and not all CVCs and laboratory tests have been studied. A standard push-pull protocol for the PICU was developed, implem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 20 publications
4
7
0
Order By: Relevance
“…Combining the results of ICC and Bland Altman analysis, we can conclude that the push-pull method provides reliable laboratory results without increasing the loss of blood and pain, and there was no hemolysis observed in the paired samples. These results are consistent with previous research, 10,11 and these findings are beneficial to patients who need multiple consecutive samples taken for blood testing. 18 In our study, the hematological laboratory results were similar to those of many other studies, 8,11 and there was no significant difference in the Hct levels based on the blood collecting method or infusion status.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Combining the results of ICC and Bland Altman analysis, we can conclude that the push-pull method provides reliable laboratory results without increasing the loss of blood and pain, and there was no hemolysis observed in the paired samples. These results are consistent with previous research, 10,11 and these findings are beneficial to patients who need multiple consecutive samples taken for blood testing. 18 In our study, the hematological laboratory results were similar to those of many other studies, 8,11 and there was no significant difference in the Hct levels based on the blood collecting method or infusion status.…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with previous research, 10,11 and these findings are beneficial to patients who need multiple consecutive samples taken for blood testing. 18 In our study, the hematological laboratory results were similar to those of many other studies, 8,11 and there was no significant difference in the Hct levels based on the blood collecting method or infusion status. It seems that the push-pull method did not increase the incidence of hemodilution.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Siegal et al showed that blood sampling conservation devices or a venous arterial blood management protection device (VAMP) can significantly reduce diagnostic blood loss by up to 80% [66]. The establishment of push-pull protocols is effective to significantly reduce the amount of discarded volume [73]. Dale et al showed, almost 30 years ago, that the amount of blood for L-Thyroxin measurements in laboratory testing is about 0.06 mL but 5.9 mL was phlebotomized [58].…”
Section: Discussionmentioning
confidence: 99%
“…The push-pull sampling method is another promising blood conservation method to avoid blood wasting during sampling. Its effect on diagnostic blood loss, anemia, and transfusion remains unclear as current studies are focused on the validity of laboratory results on blood sampled by using this method compared with standard blood sampling (69)(70)(71)(72)(73).…”
Section: Discussionmentioning
confidence: 99%